Increased gall bladder volume in primary sclerosing cholangitis. Issue 4 (October 1996) - van de Meeberg, P C; Portincasa, P; Wolfhagen, F H; van Erpecum, K J; VanBerge-Henegouwen, G P
Abstract : BACKGROUND: The diagnosis of primary sclerosing cholangitis (PSC) requires invasive procedures such as liver biopsy and endoscopic retrograde cholangiography (ERC). Sonographic measurement of fasting gall bladder volume, which has been reported to be enlarged in PSC, could serve as a non-invasive screening test. METHODS: Fasting gall bladder volume was studied in patients with PSC (n = 24), primary biliary cirrhosis (PBC, n = 13), liver cirrhosis due to other causes (n = 18), ulcerative colitis (n = 15), and healthy controls (n = 23). Meal induced gall bladder emptying was studied in patients with PSC, patients with PBC, and healthy controls. RESULTS: In patients with PSC gall bladder volume was greatly enlarged (72.9 (SEM 3.7) ml) compared with healthy controls (25.4 (1.7) ml, and patients with PBC (30.9 (2.7) ml), liver cirrhosis (31.3 (4.0) ml) or ulcerative colitis (25.8 (2.0) ml) (p < 0.0005 v all). In four patients with PSC the gall bladder wall was irregularly thickened (> 4 mm) as previously described in PSC. Postprandial residual fractions (% of fasting volume) were comparable between patients with PSC (17.5 (3.7)%) and those with PBC (23.6 (7.1%) and healthy controls (12.7 (2.3)%) Although gall bladder emptying seems normal, increased biliary pressure in patients with PSC cannot be excluded. CONCLUSION: Apart from wall thickening, patients with PSC often present with enlargement of the gall bladder. Sonographic determination of fasting gall bladder volume may be a useful, non-invasive, and easy to perform tool in the evaluation of patients suspected of having PSC.